Efficacy for the Annual Relapse Rate after the Immunosuppressive Therapy in Patients Associated with Anti-AQP4 or Anti-MOG Antibody-Positive Optic Neuritis - Sotaro Mori; Takuji Kurimoto; Yusuke Murai; Kaori Ueda; Mari Sakamoto; Norio Chihara; Yuko Yamada-Nakanishi; Makoto Nakamura (Journal of Ophthalmology)
Purpose. Although oral prednisolone is the first-line treatment for preventing recurrent optic neuritis (ON) after the completion of acute-phase treatment, especially anti-aquaporin 4 (AQP4) antibody-positive ON, and anti-myelin oligodendrocyte glycoprotein (MOG) antibody-positive ON, some patients experience relapses. Immunosuppressants could be effective in reducing the recurrence rate for neuromyelitis optica spectrum disorder and MOG antibody-related diseases, but there have been few studies addressing this issue focusing on the changes in ophthalmic parameters. The objective of the study was to analyze the impact of off-label uses of immunosuppressants to reduce recurrent ON. Design. Retrospective observational study, clinical case series. Methods. We reviewed the medical charts of 11 cases (22 eyes) who underwent immunosuppressive therapy in Kobe University Hospital and compared the annualized relapse rate (ARR) before and after immunosuppressive therapy. We also evaluated the dosage of prednisolone, complications of immunosuppressants, and other visual functional ophthalmologic parameters. Results. Eleven cases in total had AQP4 antibody (9 cases) and/or MOG antibody (3 cases). One case was double positive for these antibodies. Nine patients received azathioprine and two received mycophenolate mofetil as an initial immunosuppressive therapy. The median duration of immunosuppressant treatment was 2.8 years. The median ON ARR before immunosuppressive therapy was 0.33, and this decreased significantly to 0 after the therapy (p=0.02). The dose of prednisolone was reduced from 17.8 ± 7.1 mg/day before to 5.8 ± 2.2 mg/day after immunosuppressive therapy (p<0.01). Although two patients presented with mild elevation of liver enzymes and nausea, all patients were able to continue taking the immunosuppressants. Conclusions. Immunosuppressants can potentially decrease relapses and steroid dosage in patients with anti-AQP4 or MOG antibody-positive ON without severe adverse events and the exacerbation of visual acuities.